2015
DOI: 10.1515/exell-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the relationship between word-association and learners’ lexical development with a focus on American L1 and Croatian L2 speakers

Abstract: Vocabulary acquisition is a dynamic process and there is a constant change in the way words are stored in the mental lexicon. Word association tests are used in linguistic research to observe to which extent mental mapping can be understood. This paper presents the results of a word association game consisting of seven words administered to second language speakers, and native speakers for comparative purposes. The results indicate the possibility of a link between experiences and associations, which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…A positive correlation between L2 proficiency and the proportion of encyclopedic associations was also found. Although this finding contradicted some research published earlier ( Séguin, 2015 ; Li and Wang, 2016b ), it was in agreement with Khazaeenezhad and Alibabaee’s (2013) study. To get it clear on how L2 proficiency affects the frequency and the proportion of encyclopedic responses in word associations, further research is needed.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…A positive correlation between L2 proficiency and the proportion of encyclopedic associations was also found. Although this finding contradicted some research published earlier ( Séguin, 2015 ; Li and Wang, 2016b ), it was in agreement with Khazaeenezhad and Alibabaee’s (2013) study. To get it clear on how L2 proficiency affects the frequency and the proportion of encyclopedic responses in word associations, further research is needed.…”
Section: Discussionsupporting
confidence: 57%
“…In Li and Jiang’s (2015) study, only 0.4% of phonological associations have been reported by native Chinese speakers and 0.5 and 2.8% by Australian intermediate and elementary Chinese L2 learners respectively. Séguin (2015 , p. 92) found that “phonological similarities, being rare, would not seem to be playing an important role.” The other assumption asserts that the L2 mental lexicon is highly or even mainly dependent on form-based associations. A higher percentage of form-based associations have been found in NNSs than in NSs in many previous studies ( Meara, 1978 ; Zhang, 2005 ; Fitzpatrick, 2006 ; Fu et al, 2009 ; Xie, 2009 ; Li and Wang, 2016b ; Jiang and Zhang, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations